14q32.11 microdeletion including CALM1, TTC7B, PSMC1, and RPS6KA5: A new potential cause of developmental and language delay in three unrelated patients. Issue 5 (25th February 2021) - Eno, Celeste C.; Graakjaer, Jesper; Svaneby, Dea; Nizon, Mathilde; Kianmahd, Jessica; Signer, Rebecca; Martinez‐Agosto, Julian A.; Quintero‐Rivera, Fabiola
Abstract: Three unrelated patients with similar microdeletions of chromosome 14q32.11 with shared phenotypes including language and developmental delay, and four overlapping genes ‐ CALM1, TTC7B, PSMC1, and RPS6KA5 have been presented. All four genes are expressed in the brain and have haploinsufficiency scores, which reflect low tolerance to loss of function variation. An insight on the genes in the overlapping region, which may influence the resulting phenotype has been provided. Given the three patients' similar phenotypes and lack of normal variation in this region, it was suggested that this microdeletion may be associated with developmental and language delay.